How free trade can help convert the 'Arab Spring' into permanent peace and democracy - Thorvaldur Gylfason; Inmaculada Martínez; Per Magnus Wijkman (Center for Economic Studies and ifo Institute (CESifo), 2012)
Since Jean Monnet conceived the Coal and Steel Community, free trade has successfully prevented serious conflicts in Europe between democratically governed States with market economies. After six countries established the European Community, this principle has been extended successfully to its immediate neighbours, successively enlarging the European Union to its current 27 Member States. The Union's European Neighbourhood Policy (ENP) has through the Union for the Mediterranean and the Eastern Partnership attempted to further political stability and economic development by liberalising trade between the EU and its neighbours as well as among these neighbours themselves. The Arab Spring initially improved the prospects for establishing political democracy and human rights in key countries. In response, the EU increased the emphasis in the ENP on supporting the democratization process in the Barcelona countries and on negotiating deep and comprehensive free trade agreements among the countries of the region as well as between each such country and the EU. Using a panel gravity model of trade, this paper estimates the potential for increased intra-regional trade among ten countries of the Southern and Eastern Mediterranean coast of the EU. It attempts to answer the following questions. Between which groups of countries (e.g., Agadir countries, key actual/former belligerent countries in the Middle East) is this potential largest? Is it anywhere sufficiently large to provide an incentive for these countries to integrate much more closely with each other and with the EU? Can the prospect of such closer integration provide sufficient economic benefits to encourage progress in democratisation in key countries and resolution of conflicts between key participating countries? Or are stronger incentives needed?
Keywords: F13; F15; 330; Demokratisierung; Freihandel; Wirtschaftsintegration; Außenpolitik; Friedenssicherung; EU-Europäisch; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Mittelmeerraum; Mittlerer Osten; EU-Staaten